Fast-charging lithium ion battery negative electrode and preparation method thereof, lithium ion battery

CN122552462BActive Publication Date: 2026-10-27INNER MONGOLIA SINUO NEW MATERIAL TECH CO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610684324.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-18
Publication Date
2026-10-27
Estimated Expiration
2046-05-18

AI Technical Summary

Technical Problem

[0004]本申请的主要目的在于提供一种快充锂离子电池负极及其制备方法、锂离子电池,同步解决现有石墨复合负极在快充条件下锂离子扩散动力学缓慢和界面结构稳定性差的问题,从而提升锂离子电池的快充性能与循环寿命

Benefits of technology

[0016]本申请提出的一个或多个技术方案,至少具有以下技术效果:快充锂离子电池负极包括:泡沫铜基底;复合负极材料层,涂覆于泡沫铜基底上;其中,复合负极材料层包括石墨和包覆于石墨表面的氮掺杂软碳,包括软碳源和氮源。泡沫铜基底作为支撑结构,提供了高导电性和机械强度,增强了活性材料与基底的结合力,避免了快充循环中的脱落问题,增加了稳定性;复合负极材料层涂覆于泡沫铜基底上,确保了材料层的均匀分布和紧密附着,进一步提升了整体结构稳定性;石墨作为核心活性材料,承担锂离子嵌入/脱嵌功能;包覆于石墨表面的氮掺杂软碳,通过软碳源和氮源生成均匀的软碳层,为锂离子提供了快速扩散通道,并结合氮源实现高效掺杂,将氮原子均匀引入软碳晶格中,形成大量缺陷位点,这些缺陷位点能够增强对锂离子的吸附能力、降低锂离子扩散能垒,氮掺杂软碳包覆在石墨表面形成了稳定的界面保护膜,改善了石墨表面的化学活性和离子传输效率。因此,本申请实施例同步提升了石墨复合负极的锂离子电池的锂离子迁移效率和界面结构稳定性,从而提升锂离子电池的快充性能与循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122552462B_ABST
    Figure CN122552462B_ABST
Patent Text Reader

Abstract

The application discloses a fast-charging lithium ion battery negative electrode and a preparation method thereof and a lithium ion battery, and relates to the technical field of lithium battery preparation. The fast-charging lithium ion battery negative electrode comprises a foamed copper substrate, and a composite negative electrode material layer coated on the foamed copper substrate. The composite negative electrode material layer comprises graphite and nitrogen-doped soft carbon coated on the surface of the graphite, and the nitrogen-doped soft carbon comprises a soft carbon source and a nitrogen source. The lithium ion migration efficiency and the structural stability of the fast-charging lithium ion battery are simultaneously improved, so that the fast-charging performance and the cycle life of the lithium ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium battery technology, and in particular to a fast-charging lithium-ion battery anode and its preparation method, and a lithium-ion battery. Background Technology

[0002] With the rapid development of the new energy industry, lithium batteries have become a core energy carrier in new energy vehicles, consumer electronics, and energy storage systems due to their advantages such as high energy density, long cycle life, no memory effect, and environmental friendliness. Among these advantages, fast charging performance is one of the key performance indicators of lithium batteries.

[0003] As a core component of fast-charging lithium batteries, the anode plays a crucial role in lithium-ion insertion / extraction and electron transport. Currently, graphite-based materials are the main anode materials for lithium batteries. Although graphite anodes are low-cost and have good conductivity, their layered structure leads to a low lithium-ion diffusion coefficient, making them prone to lithium deposition during fast charging. Coating the graphite surface to form a graphite composite anode can improve kinetic efficiency, but the modification effect of existing graphite composite anode materials is poor, resulting in poor interfacial structural stability of the anode material. During long-term fast-charging cycles, the problems of slow lithium-ion diffusion kinetics and rapid battery capacity decay still exist, significantly affecting the fast-charging performance and cycle life of fast-charging lithium-ion batteries. Summary of the Invention

[0004] The main objective of this application is to provide a fast-charging lithium-ion battery anode and its preparation method, as well as a lithium-ion battery, to simultaneously solve the problems of slow lithium-ion diffusion kinetics and poor interface structure stability of existing graphite composite anodes under fast-charging conditions, thereby improving the fast-charging performance and cycle life of lithium-ion batteries.

[0005] To achieve the above objectives, this application proposes a fast-charging lithium-ion battery negative electrode, which includes: Foamed copper substrate; A composite negative electrode material layer is coated on the foamed copper substrate; The composite negative electrode material layer includes graphite and nitrogen-doped soft carbon coated on the surface of the graphite, wherein the nitrogen-doped soft carbon includes a soft carbon source and a nitrogen source.

[0006] In one feasible embodiment, the soft carbon source includes an asphalt precursor, and the nitrogen source includes urea.

[0007] In one feasible embodiment, the softening point of the asphalt precursor is 80°C to 120°C; And / or, the purity of the urea is ≥99.5%.

[0008] In one feasible embodiment, the thickness of the foamed copper substrate is 0.3mm to 2mm, and the pore size is 0.1mm to 1mm.

[0009] And / or, the loading of the composite negative electrode material on the copper foam substrate is 10 mg / cm³. 2 ~15 mg / cm 2 .

[0010] This application embodiment also provides a method for preparing the negative electrode of a fast-charging lithium-ion battery as described above, the preparation method comprising: Graphite, soft carbon source, and nitrogen source were mixed and ball-milled to obtain a mixture; The mixture is subjected to Joule heat treatment under vacuum, and nitrogen-doped soft carbon is coated on the graphite surface to obtain a composite anode material layer, wherein the nitrogen-doped soft carbon includes the soft carbon source and the nitrogen source; The composite negative electrode material layer is mixed with a conductive agent and a binder to form a negative electrode slurry, and the negative electrode slurry is coated on a foamed copper substrate to obtain a fast-charging lithium-ion battery negative electrode.

[0011] In one feasible embodiment, the graphite : the pitch precursor : the urea, by mass ratio, is (90~100):(4~6):(2~4).

[0012] In one feasible embodiment, the ball mill rotates at a speed of 600 rpm to 800 rpm for 2 hours to 3 hours. And / or, the Joule heat treatment is performed at a temperature of 1000℃~1200℃ for a time of 30s~40s.

[0013] In one feasible embodiment, the composite negative electrode material layer: the conductive agent: the binder is in a mass ratio of 94:2:4.

[0014] In one feasible embodiment, prior to the ball milling of the mixed graphite, soft carbon source, and nitrogen source to obtain the mixture, the method further includes: Needle-shaped raw coke is crushed and shaped to obtain needle-shaped coke powder, wherein the particle size of the needle-shaped coke powder is 8μm~14μm; The needle-shaped coke powder is pre-carbonized at 800℃~950℃ and graphitized at 2900℃~3000℃, and then cooled to obtain the graphite.

[0015] This application also provides a fast-charging lithium-ion battery, including the fast-charging lithium-ion battery negative electrode as described above, or the fast-charging lithium-ion battery negative electrode prepared by the fast-charging lithium-ion battery negative electrode preparation method described above.

[0016] One or more technical solutions proposed in this application have at least the following technical effects: the fast-charging lithium-ion battery anode includes: a foamed copper substrate; a composite anode material layer coated on the foamed copper substrate; wherein the composite anode material layer includes graphite and nitrogen-doped soft carbon coated on the surface of the graphite, including a soft carbon source and a nitrogen source. The copper foam substrate, serving as a supporting structure, provides high conductivity and mechanical strength, enhancing the bonding force between the active material and the substrate, preventing detachment during fast charging cycles, and increasing stability. A composite anode material layer coated on the copper foam substrate ensures uniform distribution and tight adhesion of the material layer, further improving overall structural stability. Graphite, as the core active material, performs lithium-ion insertion / extraction. Nitrogen-doped soft carbon coated on the graphite surface generates a uniform soft carbon layer through a soft carbon source and a nitrogen source, providing a rapid diffusion channel for lithium ions. Combined with the nitrogen source, efficient doping is achieved, uniformly introducing nitrogen atoms into the soft carbon lattice to form numerous defect sites. These defect sites enhance the adsorption capacity for lithium ions and reduce the lithium-ion diffusion barrier. The nitrogen-doped soft carbon coating on the graphite surface forms a stable interface protective film, improving the chemical activity and ion transport efficiency of the graphite surface. Therefore, the embodiments of this application simultaneously improve the lithium-ion migration efficiency and interface structure stability of the graphite composite anode lithium-ion battery, thereby improving the fast charging performance and cycle life of the lithium-ion battery. Attached Figure Description

[0017] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0018] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 A schematic flowchart illustrating the preparation method of the fast-charging lithium-ion battery negative electrode provided in this application embodiment; Figure 2 This is a charge / discharge test diagram of the fast-charging lithium-ion battery obtained in Example 1 of this application at 0.1C. Figure 3 This is a test graph showing the cycle stability of the fast-charging lithium-ion battery obtained in Example 1 of this application at 0.1C. Figure 4 This is a charge / discharge test diagram of the fast-charging lithium-ion battery obtained in Example 1 of this application at 2C. Figure 5 This is a rate performance test diagram of the fast-charging lithium-ion battery obtained in Example 1 of this application; Figure 6 Charge-discharge test diagram of the fast-charging lithium-ion battery obtained in Example 2 of this application at 0.1C; Figure 7 This is a test graph showing the cycle stability of the fast-charging lithium-ion battery obtained in Example 2 of this application at 0.1C. Figure 8 This is a charge / discharge test diagram of the fast-charging lithium-ion battery obtained in Example 2 of this application at 2C. Figure 9 This is a rate performance test chart of a fast-charging lithium-ion battery obtained in Example 2 of this application; Figure 10 Charge-discharge test diagram of the fast-charging lithium-ion battery obtained in Example 3 of this application at 0.1C; Figure 11 This is a test graph showing the cycle stability of the fast-charging lithium-ion battery obtained in Example 3 of this application at 0.1C. Figure 12 This is a charge / discharge test diagram of the fast-charging lithium-ion battery obtained in Example 3 of this application at 2C. Figure 13 This is a rate performance test chart of a fast-charging lithium-ion battery obtained in Example 3 of this application; Figure 14 The image shows the charge and discharge test results of the fast-charging lithium-ion battery obtained in Comparative Example 1 of this application at 0.1C. Figure 15 The graph shows the cycle stability test results of the fast-charging lithium-ion battery obtained in Comparative Example 1 of this application at 0.1C. Figure 16 This is a charge / discharge test diagram of the fast-charging lithium-ion battery obtained in Comparative Example 1 of this application at 2C. Figure 17 This is a rate performance test diagram of a fast-charging lithium-ion battery obtained in Comparative Example 1 of this application; Figure 18 The image shows the charge and discharge test results of the fast-charging lithium-ion battery obtained in Comparative Example 2 of this application at 0.1C. Figure 19 The graph shows the cycle stability test results of the fast-charging lithium-ion battery obtained in Comparative Example 2 of this application at 0.1C. Figure 20 This is a charge / discharge test diagram of the fast-charging lithium-ion battery obtained in Comparative Example 2 of this application at 2C. Figure 21 This is a rate performance test diagram of a fast-charging lithium-ion battery obtained in Comparative Example 2 of this application; Figure 22 The image shows the charge and discharge test results of the fast-charging lithium-ion battery obtained in Comparative Example 3 of this application at 0.1C. Figure 23 The graph shows the cycle stability test results of the fast-charging lithium-ion battery obtained in Comparative Example 3 of this application at 0.1C. Figure 24 This is a charge / discharge test diagram of the fast-charging lithium-ion battery obtained in Comparative Example 3 of this application at 2C. Figure 25 This is a rate performance test diagram of a fast-charging lithium-ion battery obtained in Comparative Example 3 of this application; Figure 26 The image shows the charge and discharge test results of the fast-charging lithium-ion battery obtained in Comparative Example 4 of this application at 0.1C. Figure 27 The graph shows the cycle stability test results of the fast-charging lithium-ion battery obtained in Comparative Example 4 of this application at 0.1C. Figure 28 This is a charge / discharge test diagram of the fast-charging lithium-ion battery obtained in Comparative Example 4 of this application at 2C. Figure 29 This is a rate performance test diagram of a fast-charging lithium-ion battery obtained in Comparative Example 4 of this application; Figure 30 The XRD pattern of the graphite and composite anode material of this application is shown below. Figure 31 This is a Raman diagram of the graphite and composite anode material of this application; Figure 32 Here is a SEM image of the graphite involved in the embodiments of this application; Figure 33 Here is a SEM image of the bitumen-coated graphite involved in the embodiments of this application; Figure 34 This is a SEM image of nitrogen-doped soft carbon-coated graphite involved in the embodiments of this application.

[0020] The purpose, features, and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0022] The following detailed description, with appropriate reference to the accompanying drawings, discloses the fast-charging lithium-ion battery negative electrode and its preparation method, as well as embodiments of the lithium-ion battery. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0023] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is also expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0024] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0025] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0026] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0027] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0028] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0029] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the technical solution of this application is further described below in conjunction with the accompanying drawings and embodiments. However, this application is not limited to the listed embodiments, but should also include any other well-known modifications within the scope of the claims made in this application.

[0030] The term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of this application. The phrase "in one embodiment" appearing in different places throughout this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0031] To better understand the technical solution of this application, a detailed description will be provided below in conjunction with the accompanying drawings and specific implementation methods.

[0032] As a core component of fast-charging lithium batteries, the anode material plays a crucial role in lithium-ion insertion / extraction and electron transport. Currently, graphite-based materials are the main anode materials for lithium batteries. While graphite anodes are low-cost and have good conductivity, their layered structure leads to a low lithium-ion diffusion coefficient, making them prone to lithium deposition during fast charging. Furthermore, the direct contact between the graphite surface and the electrolyte results in an unstable SEI film and reduced cycle life. Using copper foam as a three-dimensional porous current collector offers high specific surface area, excellent conductivity, and good mechanical strength, effectively reducing electrode polarization and shortening the electron transport path. However, the coating and modification effects of existing graphite composite materials are poor, resulting in insufficient lithium-ion insertion kinetics. Consequently, the bonding force between existing graphite composite materials and the copper foam substrate is weak, leading to active material shedding during long-term fast-charging cycles, causing rapid capacity decay and significantly affecting the fast-charging performance and cycle life of fast-charging lithium-ion batteries.

[0033] One or more technical solutions proposed in this application have at least the following technical effects: the fast-charging lithium-ion battery anode includes: a foamed copper substrate; a composite anode material layer coated on the foamed copper substrate; wherein the composite anode material layer includes graphite and nitrogen-doped soft carbon coated on the surface of the graphite, including a soft carbon source and a nitrogen source. The copper foam substrate, serving as a supporting structure, provides high conductivity and mechanical strength, enhancing the bonding force between the active material and the substrate, preventing detachment during fast charging cycles, and increasing stability. A composite anode material layer coated on the copper foam substrate ensures uniform distribution and tight adhesion of the material layer, further improving overall structural stability. Graphite, as the core active material, performs lithium-ion insertion / extraction. Nitrogen-doped soft carbon coated on the graphite surface generates a uniform soft carbon layer through a soft carbon source and a nitrogen source, providing a rapid diffusion channel for lithium ions. Combined with the nitrogen source, efficient doping is achieved, uniformly introducing nitrogen atoms into the soft carbon lattice to form numerous defect sites. These defect sites enhance the adsorption capacity for lithium ions and reduce the lithium-ion diffusion barrier. The nitrogen-doped soft carbon coating on the graphite surface forms a stable interface protective film, improving the chemical activity and ion transport efficiency of the graphite surface. Therefore, the embodiments of this application simultaneously improve the lithium-ion migration efficiency and interface structure stability of the graphite composite anode lithium-ion battery, thereby improving the fast charging performance and cycle life of the lithium-ion battery.

[0034] Based on this, embodiments of this application provide a negative electrode for a fast-charging lithium-ion battery, comprising: Foamed copper substrate; In one feasible embodiment, the foamed copper substrate refers to a copper material with a three-dimensional porous structure, whose internal pores are interconnected, and has high conductivity, high specific surface area and good mechanical strength, and can be used as a carrier and current collector for active materials.

[0035] In one feasible implementation, the thickness of the copper foam substrate is 0.3 mm to 2 mm, and the pore size is 0.1 mm to 1 mm.

[0036] Optionally, the thickness of the copper foam substrate can be 0.3mm, 0.5mm, 0.8mm, 1mm, 1.2mm, 1.4mm, 1.6mm, 1.8mm, 2mm, etc.

[0037] The thickness of the copper foam substrate is a key parameter affecting the overall mechanical strength, flexibility, and energy density of the anode material. An appropriate thickness ensures that the substrate maintains its structural integrity while withstanding the load of the composite anode material layer and volume changes during battery charging and discharging, preventing performance degradation due to substrate deformation or breakage. For example, an excessively thin substrate may result in insufficient mechanical strength, making it prone to deformation or breakage during cycling; while an excessively thick substrate increases the overall weight and volume of the battery, reduces energy density, and may affect lithium-ion transport pathways. Limiting the thickness of the copper foam substrate to the range of 0.3 mm to 2 mm aims to provide an optimized choice that balances mechanical strength, flexibility, and energy density.

[0038] Optionally, the pore size of the copper foam substrate can be 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, etc.

[0039] The pore size of the copper foam substrate directly affects the loading capacity, coating uniformity, and lithium-ion transport efficiency of the composite anode material layer. An appropriate pore size provides sufficient adhesion space and anchoring points for the composite anode material, enhancing the bonding force between the material and the substrate and effectively inhibiting the shedding of active material during cycling. Furthermore, the three-dimensional porous structure formed by a moderate pore size facilitates sufficient electrolyte wetting and rapid lithium-ion transport, reducing charge transfer resistance and thus improving the battery's fast-charging performance. For example, excessively small pore sizes may lead to insufficient slurry penetration, resulting in uneven coating or internal pore blockage, affecting ion transport; while excessively large pore sizes may reduce the specific surface area of ​​the substrate, decreasing the effective loading capacity of the active material or causing poor material adhesion. In this application, the pore size of the copper foam substrate is limited to the range of 0.1 mm to 1 mm to optimize material loading, adhesion, and ion transport efficiency.

[0040] In this embodiment, the thickness of 0.3mm to 2mm ensures that the foamed copper substrate has sufficient mechanical strength and structural stability, effectively supporting the composite negative electrode material layer and resisting the stress generated during fast charging cycles. This avoids the substrate becoming fragile due to being too thin or adding unnecessary weight due to being too thick, thus maintaining the overall structural integrity of the negative electrode. Simultaneously, the pore size of 0.1mm to 1mm provides an ideal adhesion surface and three-dimensional interconnected channels for the composite negative electrode material layer, greatly promoting the uniform coating of the negative electrode slurry and the firm anchoring of the active material. This significantly enhances the bonding force between the composite negative electrode material and the foamed copper substrate, effectively suppressing the shedding of the active material during fast charging cycles.

[0041] A composite negative electrode material layer is coated on a copper foam substrate; The composite anode material layer includes graphite and nitrogen-doped soft carbon coated on the graphite surface, including a soft carbon source and a nitrogen source.

[0042] In one feasible embodiment, the composite negative electrode material layer refers to a negative electrode active material layer composed of multiple materials, which is coated on a copper foam substrate for lithium ion insertion and extraction and is the core part of battery energy storage.

[0043] In one feasible implementation, the soft carbon source includes an asphalt precursor, and the nitrogen source includes urea.

[0044] Soft carbon source refers to starting material that can be converted into soft carbon after heat treatment. Soft carbon has an amorphous structure and a large interlayer spacing.

[0045] Optionally, the asphalt precursor includes petroleum asphalt, coal tar pitch, mesophase asphalt, etc. After carbonization, the asphalt has a high residual carbon content, forming a continuous and dense coating layer; furthermore, the asphalt precursor is thermoplastic and easy to coat, softening and adhering to the graphite surface during ball milling; furthermore, the carbon material after carbonization of the asphalt precursor has a similar chemical structure to graphite, resulting in a strong interfacial bond.

[0046] Optionally, urea has a nitrogen content as high as 46.7% and rapidly pyrolyzes within the temperature range of 200-400℃, enabling it to quickly release active nitrogen species during Joule heat treatment, simultaneously with pitch carbonization, achieving efficient in-situ doping. Secondly, urea has good dispersibility; when ball-milled with pitch and graphite, urea crystals can be uniformly distributed in the pitch pre-coating layer, achieving synergistic doping and coating during heat treatment, thereby improving the material's electronic conductivity and lithium-ion adsorption capacity. As a bulk chemical raw material, urea is inexpensive, and its pyrolysis products are all gases with no solid impurities remaining, requiring no additional purification steps, making it suitable for large-scale industrial production.

[0047] In one feasible embodiment, the softening point of the asphalt precursor is 80°C to 120°C; Optionally, the softening point of the asphalt precursor can be 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, 115℃, 120℃, etc. Precisely controlling the softening point of the asphalt within the range of 80℃ to 120℃ ensures that the asphalt softens uniformly and fully wets the graphite surface during mixing and heat treatment, forming a dense and uniform coating layer. This effectively avoids problems such as uneven mixing or insufficient carbonization caused by an excessively high softening point, and premature melting and uneven coating layer caused by an excessively low softening point.

[0048] In one feasible implementation, the purity of urea is ≥99.5%.

[0049] Optionally, urea with a purity of ≥99.5% is used as the nitrogen source, which greatly reduces the introduction of impurities and ensures efficient and uniform doping of nitrogen in the soft carbon structure, thereby forming high-quality nitrogen-doped soft carbon.

[0050] This embodiment, by setting a composite negative electrode material layer and the substances in the composite negative electrode material layer, not only improves the transport rate of lithium ions in the negative electrode material and enhances the interfacial stability between the material and the electrolyte, effectively suppressing the occurrence of side reactions, but also significantly improves fast charging performance and cycle life, providing a more stable and efficient negative electrode solution for fast-charging lithium-ion batteries.

[0051] In one feasible embodiment, the loading of the composite negative electrode material on the copper foam substrate is 10 mg / cm³. 2 ~15mg / cm 2 .

[0052] Optionally, the loading capacity refers to the mass of composite anode material carried on a unit area of ​​foamed copper substrate.

[0053] Optionally, the loading of the composite anode material on the copper foam substrate can be 10 mg / cm³. 2 10.5 mg / cm 2 11mg / cm 2 11.5 mg / cm 2 12mg / cm 2 12.5 mg / cm 2 13mg / cm 2 13.5 mg / cm 2 14mg / cm 2 14.5 mg / cm 2 wait.

[0054] When the loading is too low, insufficient active material may limit battery capacity, and insufficient contact area between the active material and the copper foam substrate hinders the rapid transport of electrons and lithium ions. Conversely, when the loading is too high, the material layer becomes too thick, increasing the battery's internal resistance and lengthening the lithium ion transport path within the material layer, reducing fast-charging performance. Furthermore, an excessively thick material layer is more prone to generating significant volume expansion stress during charging and discharging, potentially leading to cracking or detachment from the substrate. The loading of the composite anode material on the copper foam substrate was precisely limited to 10 mg / cm³. 2 Up to 15 mg / cm 2 Within the specified range, it effectively solves problems such as insufficient bonding force between the material layer and the substrate, material detachment, and stress concentration caused by improper load.

[0055] This application also provides a method for preparing a fast-charging lithium-ion battery negative electrode, referring to... Figure 1 The preparation methods include: Step S10: Mix and ball-mill the graphite, soft carbon source and nitrogen source to obtain a mixture; In one feasible embodiment, the three components—graphite, soft carbon source, and nitrogen source—are thoroughly and uniformly mixed together, and the particles are refined by ball milling to ensure the uniformity of subsequent reactions and the performance of the product.

[0056] In one feasible implementation, the ball mill rotates at a speed of 600 rpm to 800 rpm for 2 hours to 3 hours.

[0057] Optionally, the ball mill rotation speed can be 600 rpm, 620 rpm, 640 rpm, 660 rpm, 680 rpm, 700 rpm, 720 rpm, 740 rpm, 760 rpm, 780 rpm, 800 rpm, etc. The ball mill rotation speed is a key parameter affecting the uniformity of material mixing and the degree of particle refinement. A suitable rotation speed can provide sufficient mechanical energy to ensure thorough mixing and dispersion of different components, and to moderately grind the particles, preventing agglomeration.

[0058] Optionally, the ball milling time can be 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, etc. The ball milling time determines the degree of mixing and grinding of the materials. Sufficient time ensures that the components are uniformly dispersed, forming a stable mixture, which lays the foundation for subsequent heat treatment.

[0059] In another feasible embodiment, before ball milling the graphite, soft carbon source, and nitrogen source in step S10 to obtain the mixture, the method further includes: Step S01: The needle-shaped raw coke is crushed and shaped to obtain needle-shaped coke powder, wherein the particle size of the needle-shaped coke powder is 8μm~14μm; In one feasible embodiment, the raw needle coke is processed into powder with a specific particle size range and good morphology. Crushing can break down large pieces of needle coke into smaller particles using mechanical forces (such as impact, shearing, and grinding), for example, a jaw crusher can be used for coarse crushing, followed by a ball mill or air jet mill for fine crushing. Shaping further optimizes the particle size distribution and morphology of the powder. Precise control of particle size helps reduce structural defects that may occur during subsequent graphitization, laying the foundation for obtaining high-performance graphite.

[0060] Optionally, the particle size of the needle-shaped coke powder can be 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, etc.

[0061] Step S02: The needle-shaped coke powder is pre-carbonized at 800℃~950℃ and graphitized at 2900℃~3000℃, and then cooled to obtain graphite.

[0062] In one feasible embodiment, the main purpose of pre-carbonization is to remove volatile substances and impurities from needle-shaped coke powder at a relatively low temperature, and to promote preliminary rearrangement of carbon atoms to form a more stable carbon framework. Pre-carbonization effectively avoids material structural expansion, cracking, or increased defects caused by the rapid release of volatiles during subsequent high-temperature graphitization, thus ensuring the production of highly crystalline graphite. Graphitization is a crucial step in transforming carbon materials from an amorphous or low-graphitized state to a highly ordered graphite crystal structure. Carbon atoms gain sufficient energy for long-range migration and rearrangement, forming graphite with high crystallinity and a layered structure. After treatment, natural cooling under an inert atmosphere or controlled cooling rate avoids thermal stress caused by rapid cooling, thereby obtaining graphite with a complete structure and excellent performance.

[0063] Optionally, the pre-carbonization temperature can be 800℃, 810℃, 820℃, 830℃, 840℃, 850℃, 860℃, 870℃, 880℃, 890℃, 900℃, 910℃, 920℃, 930℃, 940℃, 950℃, etc. If the pre-carbonization temperature is too low, volatile components in the needle coke (such as heteroatom compounds like hydrogen, oxygen, nitrogen, and sulfur) cannot be fully removed. These residual impurities will be released rapidly during subsequent high-temperature graphitization, leading to material structural expansion, cracking, or even pulverization. It will also result in insufficient initial rearrangement of carbon atoms, insufficient stability of the carbon skeleton, and affect the crystallization order of the subsequent graphitization process. Consequently, the resulting graphite has a large interlayer spacing, low graphitization degree, and its capacity is unlikely to reach the theoretical value. Conversely, excessively high pre-carbonization temperatures may cause premature over-rearrangement of carbon atoms, forming a locally ordered structure, which actually increases the resistance to long-range migration of carbon atoms during subsequent high-temperature graphitization.

[0064] Optionally, the graphitization temperature can be 2900℃, 2910℃, 2920℃, 2930℃, 2940℃, 2950℃, 2960℃, 2970℃, 2980℃, 2990℃, 3000℃, etc. If the graphitization temperature is too low, the kinetic energy gained by carbon atoms is insufficient to overcome the energy barrier required for ordered stacking between graphite layers, resulting in low graphitization and insufficient crystallinity. This leads to a large interlayer spacing in the resulting graphite, approaching a disordered layer structure, and a small reversible capacity. Furthermore, the resulting graphite has many defects and poor electronic conductivity, affecting rate performance and initial coulombic efficiency. Conversely, excessively high graphitization temperatures may lead to overgrowth of graphite crystals, resulting in excessively large grain sizes, which in turn reduces the lithium-ion diffusion rate and is detrimental to fast-charging performance.

[0065] Step S20: The mixture is subjected to Joule heat treatment under vacuum to coat the graphite surface with nitrogen-doped soft carbon to obtain a composite anode material layer, wherein the nitrogen-doped soft carbon includes a precursor and the nitrogen source. In one feasible embodiment, the mixture is subjected to Joule heat treatment under vacuum. By utilizing the rapid heating characteristics of Joule heat, the asphalt is rapidly carbonized to form soft carbon in a vacuum environment. At the same time, urea is decomposed and nitrogen is uniformly doped, forming a dense and uniform nitrogen-doped soft carbon coating layer, thus obtaining a composite anode material.

[0066] In one feasible implementation, the graphite:pitch precursor:urea ratio is (90~100):(4~6):(2~4) by mass.

[0067] Optionally, the ratio of graphite:asphalt precursor:urea, by mass, can be 90:4:2, 90:5:2, 90:6:2, 90:5:3, 90:6:3, 90:4:4, 90:5:4, 90:6:4, 100:4:2, 100:5:2, 100:6:2, 100:5:3, 100:6:3, 100:4:4, 100:5:4, 100:6:4, etc. Graphite, as the main body of the anode material, aims to provide sufficient lithium-ion insertion / extraction sites to ensure the anode material possesses high capacity characteristics. If the graphite ratio is too high, it may be detrimental to the uniform formation of the subsequent coating layer; if the ratio is too low, it will reduce the overall capacity of the material. Urea, as a nitrogen source for nitrogen doping, aims to effectively introduce nitrogen through a heat treatment process, thereby improving the activity and conductivity of the graphite surface. An appropriate amount of urea ensures efficient nitrogen doping, preventing insufficient doping from hindering modification or excessive doping from negatively impacting the graphite structure. Pitch precursors, serving as the soft carbon source for the soft carbon coating, aim to form a uniform and dense nitrogen-doped soft carbon coating on the graphite surface through Joule heat treatment. This coating not only effectively protects the graphite and improves its compatibility with the electrolyte but also provides additional lithium-ion storage sites. If the pitch proportion is too high, an excessively thick coating may form, hindering lithium-ion transport; if the proportion is too low, the coating may be incomplete and ineffective in providing protection.

[0068] In one feasible implementation, the Joule heat treatment temperature is 1000℃~1200℃ and the time is 30s~40s.

[0069] Optionally, the Joule heat treatment temperature can be 1000℃, 1020℃, 1040℃, 1060℃, 1080℃, 1100℃, 1120℃, 1140℃, 1160℃, 1180℃, 1200℃, etc. The Joule heat treatment temperature is a key parameter affecting the formation of nitrogen-doped soft carbon and the degree of graphitization. Within this temperature range, pitch can be fully carbonized to form soft carbon, and nitrogen atoms generated from urea decomposition can be effectively doped into the soft carbon structure while maintaining the structural integrity of graphite.

[0070] Optionally, the Joule heat treatment time can be 30s, 31s, 32s, 33s, 34s, 35s, 36s, 37s, 38s, 39s, 40s, etc. The Joule heat treatment time is typically 30s to 40s. The Joule heat treatment time determines the extent of the carbonization and nitrogen doping reactions. Short-duration high-temperature treatment can quickly complete the formation of soft carbon and nitrogen doping, while avoiding material structure damage or excessive energy consumption that may result from over-heat treatment.

[0071] Step S30: The composite negative electrode material layer is mixed with a conductive agent and a binder to form a negative electrode slurry, and the negative electrode slurry is coated on a foamed copper substrate to obtain a fast-charging lithium-ion battery negative electrode.

[0072] In one feasible embodiment, the prepared composite negative electrode material layer is mixed with a conductive agent and a binder in a certain proportion to form a negative electrode slurry with good rheological properties and adhesion. This slurry is then uniformly coated onto a copper foam substrate. The conductive agent is used to improve the electronic conductivity of the electrode, while the binder is used to firmly bond the active material particles, the conductive agent, and the active material to the current collector (copper foam substrate), ensuring the structural stability and cycle performance of the electrode.

[0073] In one feasible implementation, the composite negative electrode material layer: conductive agent: binder ratio is 94:2:4 by mass.

[0074] In one feasible embodiment, the composite anode material layer consists of graphite and nitrogen-doped soft carbon coated on the graphite surface. This material is capable of lithium-ion intercalation / deintercalation reactions, thereby achieving energy storage and release. As the core functional component of the anode, its main function is to provide lithium-ion storage space and reactive sites. In practical operation, the composite anode material can be ensured to have good dispersibility in the slurry, avoiding agglomeration to guarantee the uniformity of the subsequent coating layer; or its surface properties can be optimized to ensure good interfacial compatibility with the conductive agent and binder, thus forming a stable slurry system. The conductive agent is a substance added to the electrode material to improve its electronic conductivity. Its role is to construct an efficient electron transport network inside the electrode, reduce the ohmic resistance of the electrode, and ensure rapid electron transport during lithium-ion intercalation / deintercalation. The conductive agent can be a carbon material with high electronic conductivity, such as carbon black (e.g., acetylene black, Ketjen black), carbon nanotubes, or graphene; or it can be a metal powder (e.g., nickel powder, copper powder) or a conductive polymer to further enhance electron transport efficiency. A binder is a polymeric material that bonds active material particles, conductive agents, and current collectors (copper foam substrate) together. Its function is to impart structural stability to the electrode, prevent the active material from detaching during cycling, and ensure good mechanical bonding between the electrode and the current collector. Commonly used polymer binders include polyvinylidene fluoride, sodium carboxymethyl cellulose, and styrene-butadiene rubber; alternatively, they can be polyacrylonitrile or polyvinyl alcohol. In addition to providing adhesion, the binder may also possess a certain degree of electrochemical stability.

[0075] This embodiment utilizes a ball milling and Joule heat treatment process, using asphalt as the carbon skeleton source and urea as the nitrogen source, to form a nitrogen-doped soft carbon coating layer in situ on the graphite surface. During the ball milling stage, physical pre-coating occurs. Asphalt particles soften and become sticky under mechanical force and localized temperature rise, spontaneously wetting and adhering to the graphite particle surface through π-π conjugation interactions, forming a uniform precursor thin layer. Then, heating releases active nitrogen from urea. These active nitrogen species exhibit high reactivity at high temperatures, reacting with carbon materials to introduce nitrogen atoms into the carbon lattice. In the high-temperature carbonization stage, the material rapidly reaches the asphalt carbonization temperature under ultra-rapid heating. The asphalt quickly melts, cross-links, and transforms in situ into a continuous amorphous soft carbon layer. Simultaneously, urea rapidly decomposes upon heating, releasing highly active nitrogen species. During asphalt carbonization, these active nitrogen species react in situ with the carbon skeleton, uniformly introducing pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen into the carbon lattice, achieving simultaneous nitrogen doping and soft carbon coating. Furthermore, the vacuum environment facilitates the rapid escape of gases generated during urea decomposition, preventing the re-adsorption of impurities on the material surface. Conventional doping processes involve first preparing carbon materials (such as graphite, soft carbon, and hard carbon), and then introducing nitrogen through external means. This results in uneven nitrogen distribution, with high nitrogen content on the surface and low nitrogen content internally. Nitrogen atoms must diffuse from the outside into the carbon framework, limiting the diffusion depth. In this embodiment, the in-situ doping process directly involves nitrogen atoms in the construction of the carbon framework, eliminating the diffusion process from the outside to the inside. Therefore, nitrogen is evenly distributed throughout the coating layer, effectively avoiding the concentration gradient problem of high surface nitrogen content and low internal nitrogen content that often occurs with external doping. Further, the ultrafast characteristics of Joule heat treatment cause the reaction to stop immediately after rapid carbonization of the pitch, inhibiting long-range rearrangement of carbon atoms and effectively preserving the amorphous structure and large interlayer spacing of soft carbon. This yields a composite anode material. Subsequent grinding and sieving further remove impurities, ensuring uniform particle size of the composite anode material and improving the preparation quality of the anode sheet and the bonding strength between the active material and the copper foam substrate. Furthermore, the introduction of a nitrogen-doped soft carbon coating layer imbues the surface of the composite anode material with abundant oxygen / nitrogen functional groups. These functional groups generate additional chemical interactions with the binder and the copper foam substrate. Combined with the physical anchoring effect of the three-dimensional structure of the copper foam, this results in a strong bond between the active material and the copper foam substrate. The preparation process in this embodiment is simple, highly controllable, uses readily available and low-cost raw materials, and requires no complex equipment or cumbersome steps, making it suitable for large-scale industrial production. The resulting fast-charging lithium-ion battery anode exhibits excellent performance.

[0076] This application also provides a fast-charging lithium-ion battery, including the fast-charging lithium-ion battery negative electrode involved in the above embodiments and the fast-charging lithium-ion battery negative electrode obtained by the above-mentioned fast-charging lithium-ion battery negative electrode preparation method.

[0077] To enable those skilled in the art to clearly understand the details and operations of the above embodiments of this application, and to demonstrate the significant improvement in the performance of the fast-charging graphite anode material preparation method of the embodiments of this application, the above technical solutions are illustrated below through multiple embodiments and comparative examples.

[0078] Example 1 Needle-shaped raw coke is crushed and shaped to obtain needle-shaped coke powder, wherein the particle size of the needle-shaped coke powder is 10 μm; The needle-shaped coke powder was subjected to low-temperature pre-carbonization treatment at 850℃, and then fed into an Atchison furnace for high-temperature graphitization treatment at 2950℃. After cooling, graphite was obtained.

[0079] Graphite, mesophase pitch and urea were mixed in a mass ratio of 95:5:3 and ball-milled at a speed of 700 rpm for 2.5 hours to obtain a mixture, wherein the softening point of the pitch was 100℃. The mixture was subjected to Joule heat treatment under vacuum at a temperature of 1100℃ for 35 seconds. After heat treatment, it was ground and sieved to obtain a composite anode material layer. A composite negative electrode material layer was mixed with a conductive agent and a binder at a mass ratio of 94:2:4 to prepare a negative electrode slurry. This slurry was then coated onto a copper foam substrate, with the composite negative electrode material loading on the copper foam substrate being 12 mg / cm³. -2 The copper foam substrate is 0.5 mm thick and has a pore size of 0.3 mm. After drying and rolling, it becomes the negative electrode of a fast-charging lithium-ion battery.

[0080] Reference Figures 2 to 5 The fast-charging lithium-ion battery anode prepared in Example 1 achieves a first-cycle discharge specific capacity of 376.8 mAh g at 0.1C. -1 The initial coulombic efficiency reached 95.9%, the capacity retention rate after 100 charge-discharge cycles was 90.3%, and the 2C / 0.1C rate of return was 89.1%.

[0081] Example 2 The needle-shaped raw coke is crushed and shaped to obtain needle-shaped coke powder, wherein the particle size of the needle-shaped coke powder is 8μm; The needle-shaped coke powder was subjected to low-temperature pre-carbonization treatment at 800℃, and then fed into an Atchison furnace for high-temperature graphitization treatment at 2900℃. After cooling, graphite was obtained.

[0082] Graphite, mesophase pitch and urea were mixed in a mass ratio of 90:4:2 and ball-milled at a speed of 600 rpm for 2 hours to obtain a mixture, wherein the softening point of the pitch was 80℃. The mixture was subjected to Joule heat treatment under vacuum at a temperature of 1000℃ for 30 seconds. After heat treatment, it was ground and sieved to obtain a composite anode material layer. A composite negative electrode material layer was mixed with a conductive agent and a binder at a mass ratio of 94:2:4 to prepare a negative electrode slurry. This slurry was then coated onto a copper foam substrate, with the composite negative electrode material loading on the copper foam substrate being 10 mg / cm³. -2 The copper foam substrate is 0.5 mm thick and has a pore size of 0.3 mm. After drying and rolling, it becomes the negative electrode of a fast-charging lithium-ion battery.

[0083] Reference Figures 6 to 9 The fast-charging lithium-ion battery anode prepared in Example 2 exhibits a first-cycle discharge specific capacity of 370.2 mAh g⁻¹ at 0.1C. -1 The initial coulombic efficiency reached 95.0%, and the capacity retention rate after 100 charge-discharge cycles was 90.5%; the 2C / 0.1C rate of return was 89.8%.

[0084] Example 3 Needle-shaped raw coke is crushed and shaped to obtain needle-shaped coke powder, wherein the particle size of the needle-shaped coke powder is 14μm; The needle-shaped coke powder was subjected to low-temperature pre-carbonization treatment at 950℃, and then fed into an Atchison furnace for high-temperature graphitization treatment at 3000℃. After cooling, graphite was obtained.

[0085] Graphite, mesophase pitch and urea were mixed in a mass ratio of 100:6:4 and ball-milled at a speed of 800 rpm for 3 hours to obtain a mixture, wherein the softening point of the pitch was 120℃. The mixture was subjected to Joule heat treatment under vacuum at a temperature of 1200℃ for 40 seconds. After heat treatment, it was ground and sieved to obtain a composite anode material layer. A composite negative electrode material layer was mixed with a conductive agent and a binder at a mass ratio of 94:2:4 to prepare a negative electrode slurry. This slurry was then coated onto a copper foam substrate, with a composite negative electrode material loading of 15 mg / cm³ on the copper foam substrate. -2 The copper foam substrate is 0.5 mm thick and has a pore size of 0.3 mm. After drying and rolling, it becomes the negative electrode of a fast-charging lithium-ion battery.

[0086] Reference Figures 10 to 13 The fast-charging lithium-ion battery anode prepared in Example 3 exhibits a first-cycle discharge specific capacity of 368.2 mAh g⁻¹ at 0.1C. -1 The initial coulombic efficiency reached 95.2%, and the capacity retention rate after 100 charge-discharge cycles was 91.2%; the 2C / 0.1C rate of return was 88.8%.

[0087] Comparative Example 1 The difference from Example 1 is that conventional copper foil is used as the substrate.

[0088] Reference Figures 14 to 17 The fast-charging lithium-ion battery anode prepared in Comparative Example 1 achieved a first-cycle discharge specific capacity of 347.5 mAh g⁻¹ at 0.1C. -1 The initial coulombic efficiency reached 80.1%, the capacity retention rate after 100 charge-discharge cycles was 72.3%, and the 2C / 0.1C rate of return was 70.7%.

[0089] Comparative Example 2 The difference from Example 1 is that graphite and mesophase pitch are mixed and ball-milled at a mass ratio of 95:5 without the addition of urea.

[0090] Reference Figures 18 to 21 The fast-charging lithium-ion battery anode prepared in Comparative Example 2 exhibits a first-cycle discharge specific capacity of 293.3 mAh g⁻¹ at 0.1C. -1 The initial coulomb efficiency reached 74.5%, the capacity retention rate after 100 charge-discharge cycles was 55.4%, and the 2C / 0.1C rate of return was 70.4%.

[0091] Comparative Example 3 The difference from Example 1 is that a conventional tube furnace was used for high-temperature carbonization in a vacuum environment at 1100°C for 2 hours to obtain a composite negative electrode material layer.

[0092] Reference Figures 22 to 25 The fast-charging lithium-ion battery anode prepared in Comparative Example 3 achieved a first-cycle discharge specific capacity of 271.7 mAh g⁻¹ at 0.1C. -1 The initial coulomb efficiency reached 75.7%, the capacity retention rate after 100 charge-discharge cycles was 56.1%, and the 2C / 0.1C rate of return was 69.7%.

[0093] Comparative Example 4 The difference from Example 1 is that the nitrogen source is ammonium chloride.

[0094] Reference Figures 26 to 29 The fast-charging lithium-ion battery anode prepared in Comparative Example 4 exhibits a first-cycle discharge specific capacity of 298.6 mAh g⁻¹ at 0.1C. -1 The initial coulomb efficiency reached 73.9%, the capacity retention rate after 100 charge-discharge cycles was 52.6%, and the 2C / 0.1C rate of return was 65.3%.

[0095] The fast-charging lithium-ion battery negative electrodes obtained from the above embodiments and comparative examples were assembled into lithium-ion batteries. The performance of the lithium-ion batteries was tested at 0.1C, and the results are shown in Table 1 below.

[0096] Table 1 Performance test results of the examples and comparative examples

[0097] As shown in Table 1 above, the composite materials prepared in Examples 1-3 all exhibit good fast-charging performance and cycle stability of lithium batteries. Compared with the comparative example, in Example 1, the conventional copper foil substrate lacks a three-dimensional conductive structure, cannot effectively reduce electrode polarization, has insufficient electron transport efficiency, and exhibits weak bonding between the active material and the substrate, resulting in inferior fast-charging performance and cycle stability compared to the foamed copper substrate. Compared with Comparative Example 2, in Example 2, the addition of urea for nitrogen doping can introduce defect sites, increase the conductivity and lithium-ion migration efficiency of the composite negative electrode material, and improve fast-charging performance and cycle stability. Compared with Comparative Example 3, in Example 1, Joule heat treatment can fully carbonize to form soft carbon, and the nitrogen atoms generated by urea decomposition can be effectively doped into the soft carbon structure while maintaining the structural integrity of graphite and shortening the heat treatment time. Compared with Comparative Example 4, in Example 1, ammonium chloride, as a nitrogen source, easily produces chloride ion residues during pyrolysis, which can contaminate the electrode material, damage the stability of the battery SEI film, and reduce the battery cycle life.

[0098] Figure 30 The results show that pure graphite exhibits a sharp (002) diffraction peak at 2θ≈26.4°, and clear (100) / (101), (004), and (110) characteristic peaks at 43°, 55°, and 77°, indicating its highly ordered hexagonal crystal structure. The composite anode material retains all the characteristic diffraction peaks of graphite, but the intensity of each peak is significantly reduced and the peak shape is significantly broadened, while the (002) peak position does not shift significantly. This indicates that nitrogen doping and soft carbon coating do not destroy the main layered structure of graphite, but introduce a large number of structural defects, reducing the crystallinity and crystallite size of graphite. Moreover, nitrogen doping mainly occurs on the graphite surface or at edge sites, without significantly changing the interlayer spacing.

[0099] Figure 31 The results show that pure graphite samples are at approximately 1350 cm⁻¹. - ¹ and ~1580 cm - ¹ Peaks D and G appear at points ¹ and are located at ~2700 cm⁻¹. - The characteristic 2D peaks of graphite were observed at position ¹, exhibiting a sharp G peak and a relatively weak D peak, with an ID / IG ratio of only 0.21, indicating a high degree of graphitization. In the Raman spectrum of the composite material, the G peak and 2D peaks remained clearly visible, proving that the ordered structure of the graphite framework was effectively preserved. The ID / IG ratio increased to 0.31, and the D peak intensity significantly increased. Furthermore, the 2D peak broadened and its intensity decreased, all due to the amorphous soft carbon layer coating the surface and the lattice defects introduced by nitrogen doping. This confirms the successful coating of nitrogen-doped soft carbon on the graphite surface.

[0100] Figures 32 to 34 The results show that pure graphite exhibits a dense, large-scale sheet structure, while the surface roughness increases slightly after being coated with pitch. Upon the introduction of urea, the sample sheets become significantly thinner, with increased wrinkles, and numerous edge defects and porous structures appear. This indicates that the nitrogen-containing atmosphere generated by urea decomposition etches the carbon framework during Joule heating, providing reaction sites for nitrogen doping.

[0101] The experimental results above show that the embodiments of this application achieve significant improvement in rate performance and cycle stability while maintaining the high capacity of lithium batteries.

Claims

1. A fast-charging lithium-ion battery negative electrode, characterized in that, The negative electrode of the fast-charging lithium-ion battery includes: Copper foam substrate; A composite negative electrode material layer is coated on the foamed copper substrate; The composite negative electrode material layer includes graphite and a nitrogen-doped soft carbon coating layer formed in situ on the graphite surface by a pitch precursor and urea under vacuum conditions through Joule heat treatment. The Joule heat treatment temperature is 1000℃~1200℃ and the time is 30s~40s.

2. The fast-charging lithium-ion battery negative electrode as described in claim 1, characterized in that, The softening point of the asphalt precursor is 80℃~120℃; And / or, the purity of the urea is ≥99.5%.

3. The fast-charging lithium-ion battery negative electrode as described in claim 1, characterized in that, The thickness of the foamed copper substrate is 0.3mm~2mm, and the pore size is 0.1mm~1mm; And / or, the loading of the composite negative electrode material on the copper foam substrate is 10 mg / cm³. 2 ~15 mg / cm 2 .

4. A method for preparing a fast-charging lithium-ion battery negative electrode as described in any one of claims 1 to 3, characterized in that, The preparation method includes: Graphite, pitch precursor and urea are mixed and ball-milled to obtain a mixture; The mixture was subjected to Joule heat treatment under vacuum to form a nitrogen-doped soft carbon coating layer on the graphite surface in situ, thus obtaining a composite anode material layer. The composite negative electrode material layer is mixed with a conductive agent and a binder to form a negative electrode slurry, and the negative electrode slurry is coated on a foamed copper substrate to obtain a fast-charging lithium-ion battery negative electrode.

5. The method for preparing the negative electrode of a fast-charging lithium-ion battery as described in claim 4, characterized in that, By mass ratio, the graphite: the pitch precursor: the urea = (90~100):(4~6):(2~4).

6. The method for preparing the negative electrode of a fast-charging lithium-ion battery as described in claim 4, characterized in that, The ball mill operates at a speed of 600 rpm to 800 rpm for 2 to 3 hours.

7. The method for preparing the negative electrode of a fast-charging lithium-ion battery as described in claim 4, characterized in that, By mass ratio, the composite negative electrode material layer: the conductive agent: the binder = 94:2:

4.

8. The method for preparing the negative electrode of a fast-charging lithium-ion battery as described in claim 4, characterized in that, Before the process of ball milling the graphite, pitch precursor, and urea to obtain a mixture, the method further includes: Needle-shaped raw coke is crushed and shaped to obtain needle-shaped coke powder, wherein the particle size of the needle-shaped coke powder is 8μm~14μm; The needle-shaped coke powder is pre-carbonized at 800℃~950℃ and graphitized at 2900℃~3000℃, and then cooled to obtain the graphite.

9. A fast-charging lithium-ion battery, characterized in that, It includes the fast-charging lithium-ion battery anode as described in any one of claims 1 to 3, or the fast-charging lithium-ion battery anode prepared by the method described in any one of claims 5 to 8.

Citation Information

Patent Citations

  • Nitrogen-doped carbon nanotube loaded bimetallic selenide material and preparation method and application thereof

    CN120483117A

  • Nitrogen-doped graphene-coated silicon-carbon composite material, and preparation method therefor and use thereof

    WO2024031867A1